Learning curve and outcome of laparoscopic transcystic common bile duct exploration for choledocholithiasis. Issue 13 (23rd September 2015) - Zhu, J G; Han, W; Guo, W; Su, W; Bai, Z G; Zhang, Z T
Abstract: Background: The best approach for cholecystocholedocholithiasis remains a matter of debate. The aim of this study was to evaluate the technical aspects, learning curve and outcome of laparoscopic transcystic common bile duct exploration (LTCBDE). Methods: Patients who underwent laparoscopic cholecystectomy with LTCBDE between January 2007 and December 2012 were identified from an institutional database. Data on preoperative investigations, intraoperative and postoperative findings were retrieved retrospectively from the patients' hospital notes. Results: There were 399 women (56·4 per cent) and 309 men (43·6 per cent), with a median age of 58 (range 18–87) years. Microincision (incision of the cystic duct at the confluence with the common bile duct (CBD) with extension of only 3–5 mm at the lateral margin of the CBD) and lithotripsy were used in the transcystic exploration in 119 patients, and increased the success rate of LTCBDE from 74·2 to 91·0 per cent. The median duration of operation was 85 (i.q.r. 65–120) min and the median postoperative hospital stay was 2 (1–3) days. Retained common bile duct stones were observed in 13 patients, and postoperative complications developed in 27 patients. The cumulative sum duration of operation learning curve comprised two phases; phase 1 included the first 250 patients and phase 2 the remaining 458 patients. Duration of operation and postoperative hospital stay decreased with increasing volume per surgeon. Recurrence of common bile duct stones was diagnosed in 26 patients during a median follow-up of 4 years. Conclusion: LTCBDE with or without microincision and/or lithotripsy is a safe and effective approach. Abstract : Safe and effective